Consequences of microgial priming in the hipothalamus. Phamacologic modulation by CSF1 receptor inhibition. - León-Rodríguez, Ana (UMA Editorial, 2025)
Neuroinflammation refers to the inflammatory response occurring in the central nervous system. It contributes to the elimination of any triggering stimulus and to the restoration of homeostasis. Microglial cells play a fundamental role: upon detecting an alteration, they undergo morphological and functional changes that lead to their activation. Once homeostasis is restored, they should return to their original surveillance state. However, in certain cases they may acquire a “primed” state characterized by hyper-reactive responses to subsequent stimuli, which can become neurotoxic and result in structural, functional, cognitive, and emotional impairments. This work aims to understand microglial priming and its consequences, and to explore strategies to control primed microglia. The microbial enzyme neuraminidase (NA) injected in the lateral ventricle of rodents mimics a microbial infection in the brain and provokes an acute inflammatory process. Although neuroinflammation is largely resolved after 2-3 weeks, subtle consequences may persist over time, possibly related to microglial priming. Previous reports describe similar outcomes in other models of acute neuroinflammation, such as the midline diffuse traumatic brain injury (TBI). This thesis project includes a series of experiments aimed at characterizing microglial priming in the hypothalamus, as a result of the neuroinflammation provoked by NA injection or by diffuse TBI. On the other hand, blockade of the receptor of the colony-stimulating factor 1 (CSF1R) with specific inhibitors such as PLX5622 results in a broad microglia depletion. This effect is reversible, and the brain is repopulated by naïve-like microglia when CSF1R signaling is restored. Nonetheless, an almost complete elimination of microglia could lead to a compromised neuroimmune response, thus jeopardizing the animal´s survival. This thesis explored a strategy of reprogramming primed microglia using a low-dose treatment with PLX5622.

The results obtained show that acute neuroinflammation induced by the injection of microbial NA produces both transient and minor persistent effects in the brain, concomitant with microglial priming in the hypothalamus and amygdala. Using two-hit experimental paradigms, it was demonstrated that a prior neuroinflammatory event sensitizes the brain to later challenges. NA-injected animals challenged with a high-fat diet displayed primed microglia in the hypothalamus, neuronal remodeling in the basal hypothalamus, and dysregulated energy balance. Besides, NA-injected rats and TBI mice exposed to acute psychological stressors, such as forced swimming or social defeat, showed enhanced hypothalamic immune activation, HPA axis sensitization, and abnormal behavioral responses. Finally, pharmacological intervention with a low dose of PLX5622, which only caused a partial microglial depletion, was able to reverse neuroimmune sensitization and prevent microglial hyper-reactivity. In conclusion, this thesis highlights the long-term consequences of hypothalamic microglial priming as a possible mechanism underlying the dysregulation of hypothalamic functions. Also, provides evidence that the CSF1R inhibitor PLX5622 used at low dose can reprogram primed microglia.
Consecuencias del condicionamiento de la microglia en el hipotálamo. Modulación farmacológica por inhibición del receptor CSF1.
Keywords: Neurología - Tesis doctorales; Neurociencias; Neurobiología molecular; Biología celular; Neurofisiología